Building Fiscal Resilience: Addressing Property Tax Challenges and Opportunities in Lemi Kura Sub-City - Teklu Kassu (PhD) (Revista Electronica de Veterinaria, 2024)
This study explores the challenges and strategic opportunities for enhancing property tax efficiency in Lemi Kura Sub-City, Ethiopia. By employing a mixed-methods approach, the research combines quantitative analysis of property tax records from 2014 to 2023 with qualitative insights from structured interviews with key stakeholders, including tax officials and property owners. The findings highlight that local governance structures, legal frameworks, economic conditions, and administrative practices play critical roles in property tax compliance. Regression analysis reveals that government spending transparency and modernized property valuation significantly impact compliance rates, whereas economic volatility presents ongoing challenges. Recommendations include reinforcing legal frameworks, implementing automated valuation systems, and engaging taxpayers through transparent communication strategies. These insights offer practical steps to improve revenue mobilization, supporting fiscal sustainability in Ethiopia’s urban centers.